A policy analysis of nurse practitioner scope of practice in Massachusetts. Issue 2 (13th February 2022) - Cuccovia, Barbara Ann; Heelan-Fancher, Lisa; Aronowitz, Teri
ABSTRACT: Nurse practitioner (NP) practice has evolved since inception of the role in 1965. Educational requirements have been standardized requiring a master's degree, yet variation in NPs scope of practice exists across the United States. As the population ages and more Americans have health insurance coverage, the demand for health care continues to increase. Shortages of clinical providers and changes in hospital models of care continue to burden the health care system. Nurse practitioners have been found to provide safe, high-quality patient care and are a potential solution to ease the burden on our health care system. Nurse practitioner scope of practice restrictions limit the ability for NPs to practice independently. The purpose of this article was to analyze the advanced practice registered nurse's (APRNs) scope of practice policy in Massachusetts (MA) where APRNs just recently obtained full practice authority. Legislation to remove NP scope of practice restrictions in MA had been presented several times but was met with resistance from physician advocacy groups stating that NPs lack the education requirements to practice independently. A recent report from the MA Health Policy Commission demonstrates the impact that NPs have on lowering health care costs and servicing individuals in underserved areas of the state. During the pandemic, restrictions on NP scope of practice in MA were temporarily removed. It was realized that if NPs can practice independently during a pandemic, then they certainly are competent to practice independently at other times. A reassessment of NP scope of practice to allow for full authority should be completed nationally.